2022
DOI: 10.1101/lm.053469.121
|View full text |Cite
|
Sign up to set email alerts
|

Stress and memory encoding: What are the roles of the stress-encoding delay and stress relevance?

Abstract: The effects of acute stress on memory encoding are complex. Recent work has suggested that both the delay between stress and encoding and the relevance of the information learned to the stressor may modulate the effects of stress on memory encoding, but the relative contribution of each of these two factors is unclear. Therefore, in the present study, we manipulated (1) acute stress, (2) the delay between stress and encoding, and (3) the relevance of the information learned to the stressor. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, we observed no overall effect of stress on episodic memory, and if anything observed a numerically opposite pattern, with the best memory performance in the Stress-Delayed group. This null finding is concordant with prior demonstrations that memory for neutral, non-stress-relevant information, such as the scene photographs in this study, is largely unaffected by pre-learning stress (Domes et al, 2004;Zoladz et al, 2011;Shields et al, 2022), suggesting that this design may not have been ideal to capture episodic memory changes.…”
Section: Stress Effects On Episodic Memorysupporting
confidence: 91%
“…However, we observed no overall effect of stress on episodic memory, and if anything observed a numerically opposite pattern, with the best memory performance in the Stress-Delayed group. This null finding is concordant with prior demonstrations that memory for neutral, non-stress-relevant information, such as the scene photographs in this study, is largely unaffected by pre-learning stress (Domes et al, 2004;Zoladz et al, 2011;Shields et al, 2022), suggesting that this design may not have been ideal to capture episodic memory changes.…”
Section: Stress Effects On Episodic Memorysupporting
confidence: 91%
“…Human studies indicated that lower levels of stress during or prior to learning may facilitate the encoding of declarative memories (Domes et al, 2002; Smeets et al, 2007). It has also been suggested that relevance of the information learned to the stressor may modulate the effects of stress on memory encoding (Shields et al, 2022). In this context, the effects of stress are observed to be stronger for emotional/arousing information as compared to neutral information (Schwabe et al, 2008; Zoladz et al, 2011).…”
Section: Stress and Cholinergic Shpmentioning
confidence: 99%
“…Memory encoding follows central or peripheral paths [24]. The central path is associated with the frontal cortex of the brain and results in the intentional, effortful, rational, and conscious processing of information [25,26]. Information processed centrally tends to last longer in the memory system of the individual [27].…”
Section: Memory Encodingmentioning
confidence: 99%